MODERNISASI PENDIDIKAN ISLAM: SKETSA PESANTREN - Zaini Dahlan (Universitas Islam Negeri Sumatera Utara Medan, 2018)
Pesantren is an educational institution that has a long and unique history. Historically, pesantren were among the earliest Islamic educational institutions and still survive today. In contrast to educational institutions that emerged later, pesantren have been very instrumental in printing ulama cadres and then play an active role in the spread of Islam and the transfer of knowledge. However, in its development the pesantren has undergone a transformation that allows it to lose its identity if its traditional values are not preserved. Today the existence of pesantren has experienced such a development that the intended components are increasingly increasing and equipped with infrastructure and facilities. In its growth history, pesantren have undergone several phases of development including the existence of pesantren specifically mixing with these developments. This paper simply discusses the modernization of Islamic education in pesantren, which then reinforces it with the objectives, curriculum, human resources, learning methods, institutions, infrastructure and facilities and the resulting changes.